What are the ethical issues related to telerehabilitation? A critical interpretive synthesis protocol - Marie-Josée Drolet (BMJ Open, 2025)
Introduction Telerehabilitation (also known as virtual rehabilitation) refers to the use of telecommunication technologies to deliver remote rehabilitation services synchronously or asynchronously to patients. Systematic reviews seem to validate the efficacy and efficiency of telerehabilitation services for diverse patient conditions while offering in addition potential cost savings in healthcare. However, integrating telerehabilitation into clinical settings raises several ethical issues, including the risk of exacerbating existing health inequities in the provision of care. Despite the apparent scarcity of the literature addressing ethical issues related to telerehabilitation, some of these fundamental concerns have already been discussed in health ethics publications. The main objectives of this study are therefore to first scrutinise what has been published to date and second to critically examine the way in which these dimensions have been conceptualised, especially the philosophical and ethical conceptions on which they are based.Methods and analysis To meet these objectives, we will conduct a Critical Interpretive Synthesis (CIS). By using an iterative and interactive process, a CIS aims to critically examine the literature and develop a theoretical understanding grounded in review studies. As per the steps described by Dixon-Woods, we will start by conducting a systematic search of the literature within five selected databases: CINAHL, EMBASE, MEDLINE, Web of Science and PsycINFO. The search strategy will be based on two main concepts: (1) telerehabilitation and (2) ethics. This systematic search will be completed by other research strategies: searching the list of references of selected articles and contacting experts within and outside our team’s expertise. Search results will be imported within the Covidence software to be assessed for relevance. We will include all empirical and non-empirical articles that specifically investigate or discuss the ethical dimensions of telerehabilitation. Only studies published in English and French will be included. The search and selection of the articles will be carried out interactively and inductively throughout the stages of extraction and development of a theoretical understanding of the data to fill emerging conceptual gaps. The analysis and critical synthesis will be led by the first author but carried out by our multidisciplinary research team. This study, through its critical dimension, has the potential to provide a more comprehensive overview of the many ethical issues surrounding telerehabilitation.Ethics and dissemination This review does not require ethical approval. We aim to publish the results in a peer-reviewed journal and do presentations at local, national and/or international research meetings and workshops for all stakeholders.